The guilt of the past: medievalist closures and disclosures. Issue 2 (3rd April 2017) - McWilliams, Stuart
Abstract: This article reflects playfully on poetic and periodic conceptions of the Middle Ages, with a view to establishing connections (direct as well as analogical) between the inscription of periodic claustrality and the formal structure of verse. As a means of defamiliarising the subjects at hand, the notion of authenticity is deployed in uncommon guises; in particular, the authentic is framed as 'the culpable' (that is, an agent regarded as identical with the perpetrator of past deeds). This legal or juridical sense of the word authentic (which is encoded in its etymology) provides the frame for considering various poetic and narrative techniques by which the Middle Ages have been put 'on trial' and found to be selfsame – or otherwise.